2013
DOI: 10.3390/ijerph10062348
|View full text |Cite
|
Sign up to set email alerts
|

The Soundscape Quality in Some Urban Parks in Milan, Italy

Abstract: Urban parks play an important role in preserving and promoting the health of citizens who are often exposed to noise pollution and the stress of daily life. The present study describes the main results obtained from a survey performed in five urban parks in Milan. Measurements of the acoustic environment were carried out in 29 sites together with interviews with 231 users on certain aspects of the parks not limited to merely sound. Acoustic data show that the surveyed parks mostly do not comply with the noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 13 publications
0
23
0
3
Order By: Relevance
“…Over the years, researchers have sought correlations between physical and perceptual data (e.g., Lercher & Schulte-Fortkamp, 2003;Brambilla, Gallo, & Zambon, 2013;Rychtáriková & Vermeir, 2013). However, such correlations are not necessarily useful per se.…”
Section: What Examples Of Soundscape Practices Do We Have So Far?mentioning
confidence: 99%
“…Over the years, researchers have sought correlations between physical and perceptual data (e.g., Lercher & Schulte-Fortkamp, 2003;Brambilla, Gallo, & Zambon, 2013;Rychtáriková & Vermeir, 2013). However, such correlations are not necessarily useful per se.…”
Section: What Examples Of Soundscape Practices Do We Have So Far?mentioning
confidence: 99%
“…No existe una metodología o pauta común para este tipo de estudios (Sueur and Farina, 2015). Así, en algunas ocasiones se emplean tiempos de menos de 10 minutos (Brambilla et al, 2013a;Torija et al, 2013), mientras que en otras se mide durante días de forma continua (Ambrose and Burson, 2004). Los datos del sonómetro fueron recogidos en modo "SLOW", registrando un nivel de presión sonora por segundo, y con la ponderación de dB(A).…”
Section: Caracterización Acústica Del Parque Mediante Mediciones De Sunclassified
“…Los vehículos de mantenimiento, seguridad y maquinaría utilizada en jardinería, fueron considerados por la mayor parte de los encuestados como neutrales o molestos, una vez más haciendo referencia a que a pesar de ser ruidosos, son necesarios para una buena conservación de El Retiro. La preferencia de los sonidos naturales sobre los artificiales o antropogénicos, se ha estudiado abundan- temente en la literatura y existen abundantes ejemplos en línea con los resultados obtenidos de este trabajo (Brambilla et al, 2013a;Iglesias Merchan et al, 2014;Yang and Kang, 2005). Finalmente, los usuarios de El Retiro consideraron que el nivel de molestia debido al ruido durante la visita fue bajo en más del 75% de los casos.…”
Section: Percepción Del Sonido Por Parte De Los Usuariosunclassified
“…Furthermore Brocolini showed that non-linear ANN models do not improve the explained variance in a significant way compared to linear regression models [35]. So, sometimes linear regressions are preferred [17,22,36]. In this study linear regressions have been chosen.…”
Section: Modelling Of Perceptual Variablesmentioning
confidence: 99%